Effects of temperature steps on human skin physiology and thermal sensation response - Chen, Chen-Peng; Hwang, Ruey-Lung; Chang, Shih-Yin; Lu, Yu-Ting (Building and environment, 2011)
Air-conditioning is frequently used as a means of adjusting indoor thermal environment in hot-and-humid areas. However, when entering an air-conditioned building from outdoors people may experience thermal discomfort and risk health consequence if the instantaneous change of air temperature exceeds the thermoregulatory capacity. A study was conducted to investigate the alteration in thermal perception and in thermoregulation that simultaneously occurred in response to temperature step in a thermal transient. In this study, two temperature down-steps from 32/28 to 24 °C and an up-step from 20 to 24 °C were created in a climatic chamber consisting of two microclimate-controlled rooms, and subjects were evaluated for change in thermal sensation as well as in skin physiological properties, including skin capillary blood flow (SCBF), skin moisture, transepidermal water loss (TEWL), and skin temperature over the course of acclimation. As the results show, a cold sensation overshot occurred in thermal sensation vote (TSV), skin temperature, and SCBF in 1 min after the temperature dropped from 32 to 24 °C. TSV correlated the best with skin temperature ( r = 0.60) and moderately with skin moisture and TEWL ( r = 0.42–0.54) when the temperature down-step reached 8 °C. TEWL acclimated in a two-stage pattern, demonstrating a difference between the sensational change and thermoregulation. The gender-specific influence occurred in thermoregulation but not in subjective sensation. The findings of the study suggest that thermoregulatory burden might be adequately controlled when the temperature step in thermal transition zone is limited to 4 °C or lower. ► We studied change in sensation and thermoregulation in thermal transition zone. ► A significant sensation overshot occurred in temperature down-step of 8 °C. ► Initial change of skin temperature tracked cold sensation overshot. ► Physiological feedback to thermal transient occurred after sensational adaptation. ► Gender was a factor in thermoregulation but not in sensational change.